The racial politics of bodies, nations, and knowledges - Baird, Barbara; Riggs, Damien W. (Newcastle upon Tyne, UK : Cambridge Scholars Pub., 2009)
The Racial Politics of Bodies, Nations and Knowledges takes on the urgent task of chipping away at existing racial and ethnic hierarchies that obstruct global and local movement towards human rights and social justice. It imagines subjective, social and p.
TABLE OF CONTENTS; LIST OF ILLUSTRATIONS; LIST OF TABLES; CONTRIBUTORS; ACKNOWLEDGEMENTS; INTRODUCTION; PART I; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; PART II; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; PART III; CHAPTER EIGHT; CHAPTER NINE; CHAPTER TEN; PART IV; CHAPTER ELEVEN; CHAPTER TWELVE; CHAPTER THIRTEEN; NOTES; REFERENCES; INDEX.
Includes bibliographical references (pages 282-318).
Print version record.
English.
Keywords: Australia -- Race relations -- Congresses; Race discrimination -- Australia -- Congresses; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; Race discrimination; Race relations; Australia; Cultural studies; Ethnic minorities & multicultural studies; Society & culture: general; Electronic books; Conference papers and proceedings; Electronic books